Pengaruh Gratis Ongkos Kirim, Diskon dan Pembayaran Cash on Delivery (COD) terhadap Keputusan Pembelian pada Shopee (Studi Kasus di Kecamatan Medan Sunggal) - Nasution, Nunut Rida Murni; Aramita, Finta; Meutia, Riza Fanny (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This research aims to find out the existence of e-commerce to help people meet human needs faster and more efficiently. From the various existing e-commerce, Shopee is the most popular e-commerce. The Effect of Free Shipping, Discounts and Cash On Delivery (COD) Payments on Purchase Decisions on Shopee (Case Study in Medan Sunggal District). This research aims to find out the effect of Free Shipping, Discount, and Cash on Delivery Payment on Purchase Decisions on Shopee. This type of research is a quantitative study with a data collection method using a questionnaire, with a sample of 100 respondents with the criteria of consumers who have bought from Shopee. The data was processed using the SPSS 27 analysis tool. The analysis technique used in this study is multiple linear regression analysis, t test (partial) and f test (simultaneous). The research results show: (1) Free Shipping has a significant effect on purchasing decisions on Shopee (Case Study in Medan Sunggal District (2) Discounts have a significant effect on purchasing decisions on Shopee (Case Study in Medan Sunggal District (3) Cash on Delivery has a significant effect on purchasing decisions (4) Free Shipping, Discounts and cash on delivery have a positive effect simultaneously on Purchasing Decisions on Shopee (Case Study in Medan Sunggal District.